Bahasa Inggris - Sumardi, Fitri Sepviyanti (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Introduction: Thymectomy in patients with myasthenia gravis or mediastinal tumors requires a very careful anesthesia strategy due to neuromuscular sensitivity, risk of airway compression, and possible hemodynamic instability. This systematic literature review summarizes the latest evidence on anesthesia governance, including engineering innovations and their implications for facilities with limited resources.Methodology: Literature searches were conducted through PubMed, Scopus, and Google Scholar using keywords related to